Acute Coronary Syndrome Mimicking Takotsubo Cardiomyopathy or Takotsubo Cardiomyopathy Mimicking Acute Coronary Syndrome? - Martin Chaumont; Marc Blaimont; Rachid Briki; Philippe Unger; Nadia Debbas (Case Reports in Cardiology)
A healthy 66-year-old female presented to the emergency department with acute chest pain, T-wave inversion in the anterior leads, and elevated troponin-I. Coronary angiography showed a stenosis in the midportion of the left anterior descending coronary artery (LAD), which did not wrap the left ventricle (LV) apex. LV angiography demonstrated a large LV apical akinetic systolic ballooning with a 45% ejection fraction. Fractional flow reserve (FFR) of LAD lesion was 0.71. Percutaneous intervention was performed. At six months, transthoracic echocardiography was normal. Fifteen months later, the patient presented with chest pain and a small rise in troponin-I. Coronary angiogram was unchanged. Repeat FFR in distal LAD was 0.86 and left ventriculography was normal. Diagnostic criteria for Takotsubo cardiomyopathy (TTC) require the absence of obstructive coronary artery disease. In the present case, TTC was highly suspected on the basis of typical LV apex ballooning. However, significant ischemia in the same territory was demonstrated by positive FFR, which could not be falsely positive in this context. Current TTC diagnostic criteria increase specificity for diagnosing TTC. This case reminds us that it is at the price of reduced sensitivity, since there is no reason to believe that coronary lesions may protect from TTC.